Pengembangan Media Pembelajaran Interaktif Berbasis Canva pada Materi Pencak Silat untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas Lima Sekolah Dasar - Rahmi Eka Putri; Yendrizal Yendrizal; Aldo Naza Putra; Ardo Okilanda (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aimed to develop a valid, practical, and effective Canva-based interactive learning media for Pencak Silat instruction in fifth-grade Physical Education, Sports, and Health (PJOK) at elementary schools in Padang Gelugur District, Pasaman Regency, in response to the low cognitive learning outcomes observed, where 70% of students failed to meet the Minimum Learning Objective Achievement Criteria (KKTP). Materials and methods. The study employed a Research and Development (R&D) approach guided by the ADDIE model, integrated with a quasi-experimental non-equivalent control group pre-test/post-test design. Both classes implemented Problem-Based Learning (PBL) as the shared instructional model, in which the experimental class (SDN 08 Makmur, n=22) used Canva-based media, while the control class (SDN 15 Sontang, n=17) used standard textbooks. Data were analyzed using Jamovi 2.3 through normality tests, homogeneity tests, paired-samples t-tests, N-Gain calculations, independent-samples t-tests, and Cohen's d effect size. Results. Expert validation yielded an overall mean of 90.67% classified as very valid, instrument reliability KR-20 = 0.81, and practicality of 96.00% from the teacher and 91.42% from students, both classified as very practical. The experimental class achieved a mean N-Gain of 0.67 compared to 0.52 in the control class, with a statistically significant difference (t=2.11, df=37, p=0.042) and a pedagogically meaningful medium effect size (Cohen's d=0.68). Conlusions. The Canva-based media was found to be valid, practical, and significantly more effective than standard textbooks within a PBL framework, and constitutes the first scientifically validated Canva-based media developed specifically for Pencak Silat instruction under the Merdeka Curriculum Phase C at the elementary school level.